The low-carb baking and dessert cookbook - Solom, Ursula (John Wiley & Sons, 2004)
From Sourdough Bread, Cheese Bread Sticks, Banana Coconut Muffins, and Vanilla Cookies to Devil's Food Cake, Butterscotch Cream Pie, Peanut Butter Swirl Ice Cream, and White Walnut Fudge, The Low-Carb Baking and Dessert Cookbook is filled with more than 200 all-new, easy-to-prepare recipes for savory treats and scrumptious sweets that will satisfy your cravings while helping you slim down, shape up, and realize all the benefits of carb-controlled living--including keeping the pounds off. Each recipe features step-by-step instructions and complete nutrition information. Your whole family will love these recipes--and you'll enjoy eating all the delicious baked goods, desserts, and confections you thought you had to sacrifice for a healthy lifestyle.